1988
DOI: 10.1073/pnas.85.17.6332
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an alternating-B DNA helix and its relationship to A-tract DNA.

Abstract: The crystal structure of the synthetic DNA dodecamer CGCATATATGCG has been solved at 2.2-A resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
215
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(233 citation statements)
references
References 34 publications
15
215
0
3
Order By: Relevance
“…Characteristic shifts in position, lineshape, and intensity also occur for each of the other peaks. Calculated SXD patterns of B-form duplex models built by using d(A) 20 and d(AT) 10 sequences are almost identical (data not shown), indicating that characteristic B-and BЈ-form SXD patterns arise from conformational differences and not sequence differences.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Characteristic shifts in position, lineshape, and intensity also occur for each of the other peaks. Calculated SXD patterns of B-form duplex models built by using d(A) 20 and d(AT) 10 sequences are almost identical (data not shown), indicating that characteristic B-and BЈ-form SXD patterns arise from conformational differences and not sequence differences.…”
Section: Resultsmentioning
confidence: 84%
“…Fig. 2A shows experimental SXD patterns measured for d(AT) 10 , d(A) 20 , and d(A) 10 duplexes from top to bottom, respectively, each recorded in 100 mM NaCl solution at two temperatures, room temperature and 3°C. The detection of diffraction peaks for solution-state DNA is significant because it provides a direct measure of in situ structure and configurational dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray crystallographic characterization of relatively short DNA duplexes containing A tracts has shown that the A tract region has a narrowed minor groove and is relatively straight and rigid (4)(5)(6). The large propeller twisting observed for the adenine residues within the A tracts themselves accounts in part for the observed rigidity (7).…”
mentioning
confidence: 99%
“…In the investigation described here, we have examined these structural and energetic features in two DNA dodecamers, which have been characterized by X-ray crystallography (5,6,16). These dodecamers, 5′-CGCAAATTTGCG-3′ and 5′-CGCATATATGCG-3′ [hereafter termed A 3 T 3 and (AT) 3 , respectively], have the same base composition and, at the 5′ and 3′ ends, the same base sequence.…”
mentioning
confidence: 99%